ROLE OF PSYCHO-EMOTIVE FACTORS IN BRONCHIAL ASTHMA DEVELOPMENT AND COURSE IN CHILDREN AND TEENAGERS - A.M. Mamed"yarov; L.S. Namazova-Baranova; L.M. Kuzenkova; R.М. Torshkhoeva; E.I. Pil'gui ("Paediatrician" Publishers LLC, 2007)
.